Introduction - Toolis, Ronan (Scottish Archaeological Internet Reports, 2011)
A series of evaluations and excavations were undertaken in advance of a proposed extension to Loudon Hill Quarry. Plough-truncated prehistoric features and medieval remains were found. The report deals only with the prehistoric remains. The medieval features will be reported on elsewhere.